Perilaku Investor Syariah Milenial: Eksplorasi Melalui Pendekatan Teori Perilaku Terencana - Chamilia Tohir Nora Octavia (Sekolah Tinggi Agama Islam Al-Muntahy, 2024)
This study aims to identify and analyze the factors influencing Sharia investment behavior among the millennial generation using the Theory of Planned Behavior (TPB) approach. The main focus of this research is to understand how attitudes, social norms, and perceived behavioral control contribute to Sharia investment decisions, as well as the role of Sharia fintech platforms in facilitating these decisions. This study adopts a qualitative approach with a case study method, where data were collected through in-depth interviews with 30 millennial investors actively using Sharia investment platforms. The findings indicate that beliefs influence a positive attitude toward Sharia investment in both financial and spiritual benefits, although concerns remain regarding potentially lower returns compared to conventional investments. Social norms, particularly the influence of family and friends, play a significant role in either encouraging or discouraging investment decisions. Furthermore, perceived behavioral control suggests that the use of Sharia fintech platforms enhances investment accessibility and transparency, yet challenges persist in terms of product comprehension and risk management. The implications of this study highlight the importance of more comprehensive Sharia financial education and the strengthening of educational features within Sharia fintech applications to improve millennial investors' understanding and confidence.